FILE DIN VIAŢA UNEI BISERICI ŞI A UNUI MITROPOLIT (I) - BOLDIŞOR istoric, colaborator la Muzeul Literaturii Române „M. Kogălniceanu”, Veronica (BIBLIOPOLIS, 2020)
The author is presenting the situation around the Metropolitan Church of Bessarabia in the interwar years through the activity of the Mitroplit Gurie Grosu. In the first chapter is elucidated the problem of canonical subordination of the Church of Bessarabia after the union of the province with Romania, in 1918. Is thorough presented the statistic of the events of that period. The author analyses the difficulties in the way of Bessarabian Church unification with the Church of Old Kingdom of Romania.